Complete characterisation of two new large Xq28 duplications involving F8 using whole genome sequencing in patients without haemophilia A. Issue 1 (4th September 2021) - Jourdy, Yohann; Bardel, Claire; Fretigny, Mathilde; Diguet, Flavie; Rollat‐Farnier, Pierre‐Antoine; Mathieu, Marie‐Laure; Labalme, Audrey; Sanlaville, Damien; Edery, Patrick; Vinciguerra, Christine; Schluth‐Bolard, Caroline
Abstract: Introduction: Depending on the location of insertion of the gained region, F8 duplications can have variable clinical impacts from benign impact to severe haemophilia A phenotype. Aim: To characterize two large Xq28 duplications involving F8 incidentally detected by chromosome microarray analysis (CMA) in two patients presenting severe intellectual disability but no history of bleeding disorder. Methods: Whole genome sequencing (WGS) was performed in order to characterize the two large Xq28 duplications at nucleotide level. Results: In patient 1, a 60–73 kb gained region encompassing the exons 23–26 of F8 and SMIM9 was inserted at the int22h‐2 locus following a non‐homologous recombination between int22h‐1 and int22h‐2. We hypothesized that two independent events, micro‐homology‐mediated break‐induced replication (MMBIR) and break‐induced replication (BIR), could be involved in this rearrangement. In patient 2, the CMA found duplication from 101 to 116‐kb long encompassing the exons 16–26 of F8 and SMIM9 . The WGS analysis identified a more complex rearrangement with the presence of three genomic junctions. Due to the multiple micro‐homologies observed at breakpoints, a replication‐based mechanism such as fork stalling and template switching (FoSTeS) was greatly suspected. In both cases, these complex rearrangements preserved an intact copy of the F8 . Conclusion: This study highlights the value of WGS to characterize the genomic junction at the nucleotide level and ultimately better describe the molecular mechanisms involved in Xq28 structural variations. It also emphasizes the importance of specifying the structure of the genomic gain in order to improve genotype‐phenotype correlation and genetic counselling.